Evidence-Based Body Contouring Surgery and VTE Prevention - Swanson, Eric (Springer International Publishing, 2018)
Intended as a companion to the recently published, Evidence-Based Cosmetic Breast Surgery (978-3-319-53957-7), Evidence-Based Body Contouring Surgery and VTE Prevention once again concentrates on the science, relying on data rather than expert opinion. In his familiar detail-oriented style, Eric Swanson critically evaluates popular body contouring procedures such as liposuction, abdominoplasty, arm lifts, thigh lifts, and buttock fat transfer. The source material is published in the major peer-reviewed plastic surgery journals. The conclusions frequently challenge conventional wisdom. Fat redistribution theory is dispelled. A unique chapter titled "The Metabolic Effect of Liposuction" reveals some surprising positive effects of liposuction. The limitations of alternative nonsurgical treatments are the subject of a chapter titled "Evaluating New Technologies." A novel chapter describes SAFE (Spontaneous breathing, Avoid gas, Face up, Extremities mobile) anesthesia as a replacement for traditional general endotracheal anesthesia - lowering risk, minimizing blood loss, and reducing recovery times. The last two chapters will have many readers reconsidering traditional methods of venous thromboembolism (VTE) prevention. Chapter 12 exposes the shortcomings of risk prediction methods and routine anticoagulation. The final chapter describes the use of ultrasound for VTE surveillance. These chapters will likely find an audience among surgeons from all specialties and anesthesiologists. For scientifically inclined readers, whether seasoned surgeons or residents, this unique resource may well lead to evidence-based changes in their practices.